Analisis Nilai Islam dan Integrasi Nilai Kesehatan pada Pengembangan Teknologi Hijau: - Parmin, Syarniah; Cahyadi, Ani (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
The progress and development of the industrial revolution has brought enormous influence and change in human life. Edward Barbier in 1989 coined the idea of a green economy or Green Economy, where one of its implementations is Green Technology. The purpose of this research is to describe the integration of Islamic values and health in Green Technology. This research design is qualitative with a library research approach. The main data sources are the Qur'an, Hadith, books and journals and articles related to the theme. To achieve the accuracy of the analysis results, triangulation of the analyzed data is carried out by involving experts who are in accordance with their expertise. The results of the analysis concluded that Islamic values, namely the values of the Qur'an and Hadith and health values, are very significant to be integrated in the innovation and development of Green Technology in order to produce technology that fulfills human welfare, conserves nature and natural resources and is worthy of worship.